CITATION STYLE IN UNDERGRADUATE THESIS LITERATURE REVIEW - Dewintha, Rezza; ., Sudarsono; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This purpose of this research is to find out the citation styles in literature review that commonly used and the consistency in using it by students of English Language Education Study Program, Teacher Training and Education Faculty, Tanjungpura University Pontianak in years 2013. This research was descriptive research especially document analysis as the form of research. The sampling technique was purposive sampling. The samples were taken randomly from students who have graduated in year 2013 and have GPA 3,50 provided in English Study Program. There were seven samples. The data were collected by appliying documentary analysis, and the writer constructed instrument table to unpack evidence as tool as data collecting. The istrument used to examine the data was table of criteria of the citation formatting guidelines adapted from APA 6th Edition, MLA 7th Edition, and Penulisan Karya Ilmiah FKIP Untan 2013. The research findings shows, just one sample who write the literature review using correct citation, and consistenly. Key Word: Citation Style, Literature Review Abstrak: Penelitian ini bertujuan untuk mengetahui bentuk kutipan di dalam kajian pustaka yang biasanya digunakan dan konsistensi dari penggunaanya oleh mahasiswa Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tanjungpura, Tahun 2013. Penelitian ini adalah penelitian descriptif khususnya penelitian dokumen. Teknik sample yang digunakan adalah sampel acak dengan persyaratan. Samel diambil acak dari mahasiswa yang lulus pada tahun 2013 dengan IPK 3,50. Sample terdiri dari tujuh orang. Data dikumpulkan dengan teknik dokumen analisis, dan penulis juga membuat table instrumen untuk membongkar bukti-bukri sebagai alat pengumpul data. Instrument yang digunakan untuk mengolah data disebut table kriteria panduan format kutipan yang diadaptasi dari APA edisi ke-6, MLA edisi ke-7, dan Penulisan Karya Ilmiah FKIP 2013. Hasil penelitian menunjukkan, hanya satu sample yang memenuhi kriteria, dengan menuliskan kutipan dengan benar dan konsisten. Kata kunci: bentuk kutipan, kajian pustaka